Faktor-faktor Protektif Kesehatan Mental Remaja di Zona Konflik Iraq : Suatu Analisis Multilevel - Nurzahara Sihombing; M. Agung Rahmadi; Helsa Nasution; Luthfiah Mawar (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
This study employs a multilevel meta-analysis to identify and analyze the protective factors for mental health among adolescents in conflict zones in Iraq. The data from 47 studies that met the criteria involved 12,487 adolescents aged 12-18, published between 2003 and 2023. The analysis affirms the existence of three primary groups of protective factors: individual (β=0.42, p<0.001), family (β=0.38, p<0.001), and community (β=0.35, p<0.001). The individual factors include resilience (r=0.56, p<0.001), emotional regulation (r=0.48, p<0.001), and spirituality (r=0.45, p<0.001). Family factors encompass family cohesion (r=0.52, p<0.001) and parental support (r=0.49, p<0.001). Additionally, community factors consist of social support (r=0.47, p<0.001) and educational access (r=0.44, p<0.001). Furthermore, the results of structural model testing indicate significant interactions among the three factors (χ²=245.67, df=124, p<0.001, CFI=0.96, RMSEA=0.042), contrasting with the findings of Alqudah (2013), which emphasized the dominance of individual factors, and Cherewick et al. (2016), which focused on community factors. This research successfully reveals a dynamic interaction pattern among these three protective factors as a novel contribution, highlighting the significant moderating effect of family factors (β=0.29, p<0.001) on the relationship between individual and community factors. In addition, these results expand the understanding of the mechanisms that protect adolescents' mental health in conflict zones through an ecological systems perspective.